ANALISIS KEPATUHAN PERAWAT PADA STANDAR ASUHAN KEPERAWATAN DI UNIT RAWAT INAP KELAS III RSU PKU MUHAMMADIYAH BANTUL YOGYAKARTA TAHUN 2010 - Lestari, Citra Ega; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: A hospital is an organization of health professionals through an organized and permanent medical facilities conducting medical services, continuous nursing care, diagnosis and treatment of illnesses suffered by patients. Nurses require documentation standards as guidance and direction in maintenance recording / documentation of activities and instructions for making patterns / recording formats appropriate, evidence recording and reporting on the status of the client and used as a communication tools that is accurate and complete. Nurses are not only required to improve the quality of nursing care, but also claimed to be properly documented. Nurses often do not obey and do the routine without regard to their legality aspect, although many factors are influence documentation. This study aims to determine compliance with standards of nursing care nurse at PKU Muhammadiyah Hospital in Bantul. Methods: This was a qualitative descriptive research with a view to charging documents compliance with nursing standards of nursing care PKU Muhammadiyah Hospital in Bantul. This research was conducted with a view of nursing care standards document in May 2010. Implementation process that includes data collection, data processing, and presentation of comprehensive data and information accurately, timely, and trustworthy in the hospitalization. Results: he results seen from the documentation of nursing care standards shows that the nurses in the inpatient unit class PKU Muhammadiyah Hospital in Bantul III comply with the standards of nursing care that is 100% obedient to categorize nurses in assessment, diagnosis and planning, while 94.7% of nurses in the implementation of compliance and categorize 89.5% nurses in the evaluation categorize obedient. Conclusion: Compliance with the standards of nursing care nurse in the Inpatient Unit RSU PKU Muhammadiyah class III Bantul, has been running quite well because the nurse dutifully on the charging document nursing care standards. Key words: compliance, standards of nursing care, nurse, in patient